2013
DOI: 10.1177/1090198113477109
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Cancer Survival Rankings

Abstract: Past research has observed that certain subgroups (e.g., individuals who are overweight/obese) have inaccurate estimates of survival rates for particular cancers (e.g., colon cancer). However, no study has examined whether the lay public can accurately rank cancer survival rates in comparison with one another (i.e., rank cancers from most deadly to least deadly). A sample of 400 Indiana adults aged 18 to 89 years (M = 33.88 years) completed a survey with questions regarding perceived cancer survival rates. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Other work shows that people misunderstand the relative prevalence of different cancers, perhaps for similar reasons. 8 Although more work is needed to establish causality, these findings suggest the need to design cancer messages not only to be less ambiguous but to explicitly present health risks in the context of other health risks—consistent with the finding that people are often more responsive to comparative than absolute information. 9 Of course, such an approach would need to be tailored for subpopulations with higher cancer risk.…”
Section: Discussionsupporting
confidence: 61%
“…Other work shows that people misunderstand the relative prevalence of different cancers, perhaps for similar reasons. 8 Although more work is needed to establish causality, these findings suggest the need to design cancer messages not only to be less ambiguous but to explicitly present health risks in the context of other health risks—consistent with the finding that people are often more responsive to comparative than absolute information. 9 Of course, such an approach would need to be tailored for subpopulations with higher cancer risk.…”
Section: Discussionsupporting
confidence: 61%
“…How the news media cover cancer may bear significant implications for cancer prevention and control. Past studies suggest that the amount of news coverage of specific cancers does not correspond to the actual incidence or mortality rates ( 1 2 3 4 5 6 ) and that public perception of cancer risk is significantly related to distorted depictions in cancer news coverage ( 7 8 ). For example, Jenson and colleagues found that in comparison to cancer incidence rates in the United States, certain cancers (e.g., breast, lung, blood/Leukemia, pancreatic, and skin) were overreported in newspapers, whereas other cancers (e.g., male reproductive, female reproductive, kidney, and thyroid) were underreported ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cancer risk and preventive recommendations involve exceptional uncertainty and ambiguity (e.g., Niederdeppe & Levy, 2007), which create highly affective psychological states (Bar-Anan, Wilson, & Gilbert, 2009; Han, Moser, & Klein, 2006). Media depictions of cancer further exemplify negative affect and uncertainty (Gottlieb 2001; Niederdeppe, Fowler, Goldstein, & Pribble, 2010), potentially contributing to inaccurate beliefs about risk and mortality that are disproportionally driven by affect (Jensen, Scherr, Brown, Jones, & Christy, 2013; Klein, Ferrer, Graff, Kaufman, & Han, 2014). Thus, cancer prevention and control science can derive particular benefit from research on fundamental affective processes.…”
mentioning
confidence: 99%